Principles of molecular biology - Tropp, Burton E. (Jones & Bartlett Learning, 2014)
Includes access to the Student Companion Website with every print copy of the text. Written for the more concise course, Principles of Molecular Biology is modeled after Burton Tropp's successful Molecular Biology: Genes to Proteins and is appropriate for the sophomore level course. The author begins with an introduction to molecular biology, discussing what it is and how it relates to applications in "real life" with examples pulled from medicine and industry. An overview of protein structure and function follows, and from there the text covers the various roles of technology in elucidating the central concepts of molecular biology, from both a historical and contemporary perspective. Tropp then delves into the heart of the book with chapters focused on chromosomes, genetics, replication, DNA damage and repair, recombination, transposition, transcription, and wraps up with translation. Key Features: - Presents molecular biology from a biochemical perspective, utilizing model systems, as they best describe the processes being discussed -Special Topic boxes throughout focus on applications in medicine and technology -Presents "real world" applications of molecular biology that are necessary for students continuing on to medical school or the biotech industry -An end-of-chapter study guide includes questions for review and discussion -Difficult or complicated concepts are called-out in boxes to further explain and simplify